2019
DOI: 10.1039/c8en01362d
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous photocatalytic redox removal of chromium(vi) and arsenic(iii) by hydrothermal carbon-sphere@nano-Fe3O4

Abstract: The reduction of Cr(vi) and oxidation of As(iii) were markedly accelerated by employing iron oxide encapsulated in hydrothermal carbon sphere under simulated solar light irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…The Fe 2+ generated in equation 11 would have been an additional source of Fe 2+ for A. ferrooxidans to generate Fe 3+ , which could in turn form additional Fe 3+ precipitates. Rich Fe 2+ could maintain a relatively reducing environment and assist the oxidation of As(III) (Liu et al , 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Fe 2+ generated in equation 11 would have been an additional source of Fe 2+ for A. ferrooxidans to generate Fe 3+ , which could in turn form additional Fe 3+ precipitates. Rich Fe 2+ could maintain a relatively reducing environment and assist the oxidation of As(III) (Liu et al , 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, nano-sized, zero-valence iron (nZVI) particles and ZVI-biochar have been used for the remediation of As and Cr (Qiao et al , 2017; Vítková et al , 2018; Liu et al , 2019). Baragaño et al (2020) showed that notable results were obtained for nZVI at a dose of 2% (89.5% decrease in As, TCLP test – toxicity characteristic leaching procedure), and no negative effects on soil parameters were detected.…”
Section: Introductionmentioning
confidence: 99%
“…Iron oxide impregnated hydrothermal carbon spheres were tested for the simultaneous redox conversion and removal of Cr(VI) and As(III) from AMD using simulated solar light irradiation (Liu, Zhang, Tao, Hao, & Zhang, 2019). The AMD with Cr(III) and As(V) were readily treated by precipitation as Cr(OH) 3 and FeAsO 4 .…”
Section: Mine Drainage Remediation Technologymentioning
confidence: 99%
“…Various photocatalyst for the removal of Cr (VI) have been investigated, including active carbon [18], metal oxide nanoparticles [19,20], synthesized polymer beads [21] and agriculture waste [22]. Among these, iron oxide (Fe 3 O 4 ) is one of the most widely studied due to its high efficiency, chemical stability, low cost, and availability [23,24]. However, after photodegradation, it is extremely difficult to separate the catalyst from the solution, which would raise the operational costs [25,26].…”
Section: Introductionmentioning
confidence: 99%